Firm foundations in the knowlwdge intensive business service sector : results from a comparative empirical study in three German regions - Andreas Koch; Thomas Stahlecker (Institut für Angewandte Wirtschaftsforschung (IAW), 2004)
A key feature of the knowledge-based economy is a remarkable increase in the number of knowledge intensive business service firms (KIBS). KIBS are based upon highly specialised knowledge and they acquire knowledge in the course of the interaction process that takes place whilst they provide their services. As knowledge and its organisation are tied to personal capabilities and information, spatial ?proximity? to providers and users of knowledge appears to be crucial for the foundation and early development of KIBS. The quality of regional environments (e.g. configurations of incubator and intermediate organisations or a regional ?entrepreneurial climate?) and the foundation and development of KIBS are obviously interrelated. Based upon a standardised survey, the present paper analyses regional differences in the foundation process and early development of KIBS in three German regions in a comparative way. The results of our descriptive analysis show strong regional ties of founders and KIBS firms during the founding process as a result of spatial proximity. With only slight differences, those ties could be observed in all three regions. They are primarily related to the former activities of the founder, the transfer of results and experiences into the new firm, and spatial proximity to the most important customers or other partners within the exchange of knowledge. Major differences can be derived with regard to the development of the firms (e.g. Munich KIBS firms show a much better development in employment), obstacles in accessing the regional market, and the general assessment of the regional framework conditions from the point-of-view of the KIBS founders.
Keywords: 330; KIBS; firm foundations; interaction; spatial proximity; Germany